Pledging For The Environment: One Act At A Time - Jeff Scott; Alice Payne; M Daud Ahmed; John Horsely; Liz Sidiropoulos; Samuel Alexander; Bryan Lewis; Zuhairuse MD Darus; Rahmi Novalia; Jane Shepherd; Anamarija Frankic; Lisa Greber; et al. (Common Ground Research Networks, 2024)
The purpose of this research was to assess the value of empowering Faculty of Education students in pledging and carrying out "Acts of Green" over a four-month period. Three themes were explored including perceived personal benefit, empowerment and commitment, and attitudinal shift towards environmental education. All three themes focused around pledging to an Act of Green. The Canadian One Million Acts of Green initiative was inspired by Canadian Broadcasting Corporation television host George Stroumboulopoulos and encouraged individuals to make a personal environmental pledge resulting in changes to improve our environment and reduce greenhouse gases. The participants in the study included 320 pre-service teachers of which 80.3% (n=257) responded to the on-line anonymous survey. Significant gains were shown in the three focus areas of the study: 1) the respondents, all of whom choose their own personal Act of Green (as opposed to being told what to do) increased their commitment to follow through (89.5% (n=230)); 2) developed a positive attitude towards teaching environmental education in their classroom (91.8% (n=236)); and 3) a vast majority of the respondents would Common Ground, Jeff Scott, All Rights Reserved.